(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examines the influence of Artificial Intelligence (AI) on time optimization within Human Resource (HR) functions, focusing on how AI-driven tools enhance efficiency and organizational outcomes. With HR departments increasingly expected to act as strategic partners, the integration of AI helps automate repetitive tasks such as recruitment, payroll, and performance management, thereby reducing time consumption and improving decision-making. Using a descriptive research design, data was collected from 70 HR professionals in IT companies in Chennai through a structured questionnaire. The study highlights that AI significantly improves time efficiency, enabling HR professionals to focus more on strategic and employee-centric roles. It also addresses concerns related to adoption, ethical considerations, and human acceptance, emphasizing the need for a balanced, human-cantered approach. Overall, the research contributes to understanding how AI-powered time optimization can transform HR functions and support organizational effectiveness.